The unforgiving work environment of black African women domestic workers in a post-apartheid South Africa. Issue 2 (17th February 2023) - Dawood, Q.; Seedat-Khan, M.
ABSTRACT: In democratic South Africa, many Black African women are still subjugated by being employed as domestic workers. Increasing evidence emerged amid the COVID-19 pandemic revealing unmistakable signs of modern-day slavery among South African Black domestic workers. This paper proposes a clinical model which examines how gender, class, and race intersections affect the ways in which specifically identified change agents offer new, transforming interventions via clinical intervention. Adopting a clinical approach augments identification of a specific social problem from a scientifically systematic applied approach built on applied theory. We report on the conditions facing vulnerable Black African women using a bricolage research approach. The resulting model explicitly identifies systemic inequalities and indicates how to reduce exploitation and protect workers. The bricolage approach aided the secondary qualitative analysis of complex bonded-labour intersections. The problem of Black African women living as bonded domestic labour is augmented by the girl children's primary socialisation, Western patriarchal re-socialisation which sustains apartheid, and race, class, occupational, and gender inequalities.